Synthesis and study on biological activity of nitrogen-containing heterocyclic compounds – regulators of enzymes of nucleic acid biosynthesis - Alexeeva, I.V.; Shved, A.D. (Вiopolymers and Cell, 2013)
Results of investigations on the development of new regulators of functional activity of nucleic acid biosynthesis enzymes based on polycyclic nitrogen-containing heterosystems are summarized. Computer design and molecular docking in the catalytic site of target enzyme (T7pol) allowed to perform the directed optimization of basic structures. Several series of compounds were obtained and efficient inhibitors of herpes family (simple herpes virus type 2, Epstein-Barr virus), influenza A and hepatitis C viruses were identified, as well as compounds with potent antitumor, antibacterial and antifungal activity. It was established that the use of model test systems based on enzymes participating in nucleic acids synthesis is a promising approach to the primary screening of potential inhibitors in vitro. Узагальнено результати досліджень щодо створення нових регуляторів функціональної активності ферментів біосинтезу нуклеїнових кислот на основі поліциклічних азотовмісних гетеросистем. Комп’ютерний дизайн і молекулярний докінг у каталітичний сайт ферменту-мішені (Т7пол) дозволили провести спрямовану оптимізацію базових структур. Отримано декілька серій сполук, з-поміж яких виявлено ефективні інгібітори вірусів родини герпесу (ВПГ-2, вірус Епштейна-Барр), грипу А та гепатиту С, а також препарати з потужною протипухлинною, протибактерійною та протифунгальною дією. Визначено перспективність застосування модельних тест-систем на основі ферментів, що обслуговують синтез нуклеїнових кислот, для первинного скринінгу потенційних інгібіторів in vitro. Обобщены результаты исследований по созданию новых регуляторов функциональной активности ферментов биосинтеза нуклеиновых кислот на основе полициклических азотосодержащих гетеросистем. Компьютерный дизайн и молекулярный докинг в каталиический сайт фермента-мишени (Т7пол) позволили прове- сти направленную оптимизацию базовых структур. Получено несколько серий соединений, среди которых выявлены эффективные ингибиторы вирусов семейства герпеса (ВПГ-2, вирус Эпштейна-Барр), гриппа А и гепатита С, а также препараты с мощным противоопухолевым, антибактериальным и антифунгальным действием. Определена перспективность применения модельных тест-систем на основе ферментов, обслуживающих синтез нуклеиновых кислот, для первичного скрининга потенциальных ингибиторов in vitro.